The influence of reconstruction and attenuation correction techniques on the detection of hypoperfused lesions in brain SPECT images - Ghoorun, Shivani (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScMedSc)--Stellenbosch University, 2004.